Biological in-vivo measurement of dose distribution in patients' lymphocytes by gamma-H2AX immunofluorescence staining: 3D conformal- vs. step-and-shoot IMRT of the prostate gland - Zwicker, Felix; Swartman, Benedict; Sterzing, Florian; Major, Gerald; Weber, Klaus-Josef; Huber, Peter E; Thieke, Christian; Debus, Jürgen; Herfarth, Klaus (Radiation oncology (London, England), 2011)
Background Different radiation-techniques in treating local staged prostate cancer differ in their dose- distribution. Physical phantom measurements indicate that for 3D, less healthy tissue is exposed to a relatively higher dose compared to SSIMRT. The purpose is to substantiate a dose distribution in lymphocytes in-vivo and to discuss the possibility of comparing it to the physical model of total body dose distribution. Methods For each technique (3D and SSIMRT), blood was taken from 20 patients before and 10 min after their first fraction of radiotherapy. The isolated leukocytes were fixed 2 hours after radiation. DNA double-strand breaks (DSB) in lymphocytes' nuclei were stained immunocytochemically using the gamma-H2AX protein. Gamma-H2AX foci inside each nucleus were counted in 300 irradiated as well as 50 non-irradiated lymphocytes per patient. In addition, lymphocytes of 5 volunteer subjects were irradiated externally at different doses and processed under same conditions as the patients' lymphocytes in order to generate a calibration-line. This calibration-line assigns dose-value to mean number of gamma-H2AX foci/ nucleus. So the dose distributions in patients' lymphocytes were determined regarding to the gamma-H2AX foci distribution. With this information a cumulative dose-lymphocyte-histogram (DLH) was generated. Visualized distribution of gamma-H2AX foci, correspondingly dose per nucleus, was compared to the technical dose-volume-histogram (DVH), related to the whole body-volume. Results Measured in-vivo (DLH) and according to the physical treatment-planning (DVH), more lymphocytes resulted with low-dose exposure (< 20% of the applied dose) and significantly fewer lymphocytes with middle-dose exposure (30%-60%) during Step-and-Shoot-IMRT, compared to conventional 3D conformal radiotherapy. The high-dose exposure (> 80%) was equal in both radiation techniques. The mean number of gamma-H2AX foci per lymphocyte was 0.49 (3D) and 0.47 (SSIMRT) without significant difference. Conclusions In-vivo measurement of the dose distribution within patients' lymphocytes can be performed by detecting gamma-H2AX foci. In case of 3D and SSIMRT, the results of this method correlate with the physical calculated total body dose-distribution, but cannot be interpreted unrestrictedly due to the blood circulation. One possible application of the present method could be in radiation-protection for in-vivo dose estimation after accidental exposure to radiation.